2012
DOI: 10.1038/leu.2012.39
|View full text |Cite
|
Sign up to set email alerts
|

Valproic acid induces differentiation and transient tumor regression, but spares leukemia-initiating activity in mouse models of APL

Abstract: Aberrant histone acetylation was physiopathologically associated with the development of acute myeloid leukemias (AMLs). Reversal of histone deacetylation by histone deacetylase inhibitor (HDACis) activates a cell death program that allows tumor regression in mouse models of AMLs. We have used several models of PML-RARA-driven acute promyelocytic leukemias (APLs) to analyze the in vivo effects of valproic acid, a well-characterized HDACis. Valproic acid (VPA)-induced rapid tumor regression and sharply prolonge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 49 publications
1
41
0
1
Order By: Relevance
“…Recently it has been identified that VPA is an effective inhibitor of HDAC activity at physiologically relevant concentrations. It is also becoming evident that the efficacy of VPA in vivo is in part due to inhibition of cancer cell migration, invasion and angiogenesis (Chou et al, 2011;Wedel et al, 2011;Leiva et al, 2012). This gave us the inspiration to see whether VPA could have the similar effects in ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Recently it has been identified that VPA is an effective inhibitor of HDAC activity at physiologically relevant concentrations. It is also becoming evident that the efficacy of VPA in vivo is in part due to inhibition of cancer cell migration, invasion and angiogenesis (Chou et al, 2011;Wedel et al, 2011;Leiva et al, 2012). This gave us the inspiration to see whether VPA could have the similar effects in ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…24 Short-term in vivo treatment of preleukemic mice with the class I HDACi VPA phenocopied the effect of Hdac1 knock-down during PML-RAR-mediated leukemogenesis with expansion of the Gr1 1 /cKit 1 population and accelerated disease. Intriguingly, this phenomenon was not observed after treatment of premalignant Em-myc mice with VPA, indicating that a tumor-type or oncogene-specific effect may be at play (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…For APL mice treatment, 2*10^5 APL cells were injected intravenously into nonirradiated congenic-recipient mice (C57Bl/6-Ly5.1) and then treated with VPA (intraperitoneally at the dose of 400 mg/kg twice a day for 4 weeks) when the blast cells (Ly5.2) in peripheral blood reached 5% to 10%. 24 Quantitative polymerase chain reaction Total RNA was purified using RNeasy Mini Kit (QIAGEN, Valencia, CA), quantified and reverse transcribed. From 5 to 10 ng of cDNA were used to perform quantitative polymerase chain reaction using SYBR Green Reaction Mix (Perkin Elmer, Boston, MA).…”
Section: Pharmacologic Treatmentsmentioning
confidence: 99%
“…Complementing these studies, the HDAC inhibitor valproic acid (mainly acting on class I HDACs) was shown to behave differently at the preleukemic and leukemic stages, mimicking the HDAC1 knockdown phenotype [112]. Moreover, in established leukemia, valproic acid showed different effects on the bulk of tumor cells and LICs, being mostly effective on the bulk of APL blasts and having only a mild effect on LICs [115]. From these studies, it therefore appears that HDACs not only have different roles at different stages of tumorigenesis, but also have different biological effects in different tumor cell subtypes (LICs versus the bulk of tumor cells).…”
Section: Apl As a Paradigm For Epigenetic Therapymentioning
confidence: 99%